2013
DOI: 10.5578/keg.5259
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Computer Assisted Instruction on Elementary Reading and Writing Achievement

Abstract: ABSTRACT:The research investigated the effect of computer assisted instruction (CAI) on elementary reading and writing achievement (ERWA). The sample consisted of 64 first graders (32 in the experimental group and 32 in the control group) in the 2006-2007 academic year. This quasi-experimental study had a posttest only control group design and was conducted during the first semester. The experimental group was taught by CAI and the control group was taught by traditional instruction. Data were gathered through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
1
3
0
3
Order By: Relevance
“…Teachers stated that they used the first literacy teaching applications designed for tablets and smartphones at every stage with a focus on making the voice felt. In many studies (Birgül, 2014;Orhan-Karsak, 2014;Kaymaz & Yeşilyurt, 2020), in parallel with this study, it is seen that teachers use web-based educational software, multimedia materials and computers at every stage of the first reading and writing teaching process, including the teaching of sounds. In the study conducted by Gürol and Yıldız (2015), classroom teachers mostly prefer to use EBA and education portals at every stage, especially in preparation for teaching reading and writing, making sound felt, and forming syllables and words.…”
Section: Conclusion Discussion and Suggestionssupporting
confidence: 58%
See 3 more Smart Citations
“…Teachers stated that they used the first literacy teaching applications designed for tablets and smartphones at every stage with a focus on making the voice felt. In many studies (Birgül, 2014;Orhan-Karsak, 2014;Kaymaz & Yeşilyurt, 2020), in parallel with this study, it is seen that teachers use web-based educational software, multimedia materials and computers at every stage of the first reading and writing teaching process, including the teaching of sounds. In the study conducted by Gürol and Yıldız (2015), classroom teachers mostly prefer to use EBA and education portals at every stage, especially in preparation for teaching reading and writing, making sound felt, and forming syllables and words.…”
Section: Conclusion Discussion and Suggestionssupporting
confidence: 58%
“…Additionally, in this study, teachers stated that the first literacy teaching applications designed for smartphones and tablets negatively affected students' writing skills. When the studies conducted in this context in the literature (Orhan-Karsak, 2014;Kaymaz & Yeşilyurt, 2020) are examined, it is clearly shown that the educational software used in primary reading and writing teaching has a negative effect or no effect on students' writing skills, but computer-assisted teaching is effective in writing and punctuation. It is also possible to find relevant findings (Turunen, 2019).…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is emphasized that the use of assistive technologies in literacy teaching is very important in the literature [54] [55] [56]. Some studies indicate that technology in-creases the motivation of individuals with special needs who have reading difficulties [57] [41] [58] [59].…”
Section: Conclusion and Discussionmentioning
confidence: 99%